The Novel Use of Electrochemically Activated pH Neutral Hypochlorous Acid Solutions as Biodecontaminants for Removable PMMA Dental Prostheses. - McReynolds, David (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
Background: Polymethylmethacrylate (PMMA) is a frequently used dental material in prosthodontics and it is likely that PMMA materials will remain relevant dental materials into the future. Whilst the current gold standard fabrication procedures for PMMA prostheses use heat-processed PMMAs, cold-processed PMMAs are frequently used materials and milled PMMAs are now growing in popularity. Surface and sub-surface porosity of PMMAs in combination with poor oral and denture hygiene can result in the manifestation of clinical diseases locally and systemically. Currently, no denture cleaning or disinfection method meets the ideal criteria set out by the American College of Prosthodontists guidelines on the care and maintenance of dentures. Electrochemically activated pH neutral hypochlorous acid solutions have been shown to be effective disinfectants for contaminated surfaces, various wounds, dental unit waterlines, washbasin taps, washbasin U-bends, water network output water and for dental impressions. Such solutions have not been investigated in the literature as potential biodecontaminants for PMMA materials. The properties of such solutions may meet many of the criteria set out by the American College of Prosthodontists for an ideal denture cleanser. Aims and Objectives: To investigate if electrochemically activated pH neutral hypochlorous acid solutions could be used as an effective alternative disinfectant for conventional complete dentures (CCDs) made from cold-processed, heat-processed and milled PMMAs and to assess if a minimum 5 log10 reduction of viable microorganisms of reference bacterial and yeast strains present on PMMAs was possible by immersion disinfection in 5 ml of hypochlorous acid solution for 5 min under dirty conditions. Materials and Methods: Cold-processed, heat-processed and milled PMMA discs were fabricated by the flask and pour technique, flask, pack and press technique and by computer aided design and computer aided manufacturing (CAD/CAM) technology, respectively, as a model to represent CCDs fabricated from these materials. Discs were uniformly roughened on one surface to represent the rough intaglio surface of a CCD and uniformly polished on the opposite surface to represent the smooth polished surface of a CCD. Discs were inoculated on their uniformly roughened upper surface with 5 μl of 3% (w/v) bovine serum albumin (BSA) fraction V to simulate dirty conditions and then discs were subsequently inoculated with 45 μl of a standardised test preparation (10^10-10^14 colony forming units (CFU)) of one of the reference bacterial strains Staphylococcus aureus ATCC 6538, Enterococcus hirae ATCC 10541, Pseudomonas aeruginosa ATCC 15442 or the yeast strain Candida albicans SC5314. Inoculated discs were subjected to immersion disinfection with 5 ml of electrochemically activated pH neutral hypochlorous acid of concentrations ranging from 200 ? 1000 ppm free available chlorine (FAC) for 5 min. Three independent disinfection experiments were undertaken for each concentration of hypochlorous acid solution on each type of PMMA disc, within which three pH neutral hypochlorous acid disinfection discs were tested against a corresponding number of sodium hypochlorite disinfection discs, ortho-phthalaldehyde disinfection discs and control discs. The number of viable microorganisms remaining following each disinfection cycle was determined following recovery by serial dilution and culture on trypticase soy agar (TSA) (for bacteria) or yeast extract peptone dextrose (YEPD) agar (for yeasts). Antimicrobial efficacy was evaluated by calculating the absolute value of log10N/N0, [log(N/N0)], where N is the residual bacterial count after treatment of disinfection discs and N0 is the bacterial count in CFU/ml recovered from control discs. Results: Statistically significant (P < 0.05) reductions in viable counts (≥ 5 log10) were achieved with S. aureus ATCC 6538, E. hirae ATCC 10541, P. aeruginosa ATCC 15442 and C. albicans SC5314 when inoculated PMMA discs were immersed in 5 ml of freshly generated electrochemically activated pH neutral hypochlorous acid solution at 250 ppm FAC, at 1000 ppm FAC, at 900 ppm FAC and at 500 ppm FAC, respectively, for 5 min under dirty conditions. To achieve a statistically significant (P < 0.05) 5 log10 reduction or more in viable microorganisms on soiled PMMA surfaces, immersion disinfection within freshly generated electrochemically activated pH neutral hypochlorous acid of concentration 1000 ppm FAC for a 5 min period was advisable. This disinfection cycle appears to show comparable results to similar immersion disinfection cycles using the commercially available 2% (w/v) sodium hypochlorite disinfectant Milton Sterilising Fluid of 20,000 ppm FAC, as well as the 0.55% (v/v) ortho-phthalaldehyde hospital disinfectant Cidex? OPA. No adverse effects were visually obvious on PMMA discs in terms of bleaching, colour instability or surface degradation when discs were subjected to freshly generated electrochemically activated pH neutral hypochlorous acid solutions of concentrations of 200 ppm ? 1000 ppm FAC. Conclusion: Electrochemically activated pH neutral hypochlorous acid solutions could be used as effective alternative disinfectants for CCDs made from cold-processed, heat- processed or milled PMMAs.
APPROVED
Keywords: Electrochemically activated; Hypochlorous acid; Anolyte; Mixed Oxidant; Electrolysed functional water; Super oxidised water; PMMA; Polymethylmethacrylate; Poly(methyl methacrylate); Removable dental prosthesis; Removable partial denture; Conventional complete denture; RPD; CCD; Complete denture; Partial denture; Biodecontaminant; Disinfection